Lingkungan Keagamaan dan Praktik Pengajaran di Rumah dalam Membentuk Kefasihan Membaca Al-Qur'an di Kalangan Siswa Sekolah Dasar - Fatimah Azzahra (STKIP Subang, 2026)
Qur’anic reading fluency (tajwid, tartil, and correct articulation) is a foundational religious competency expected of Muslim elementary students, yet achievement remains low and uneven, particularly in eastern Indonesia. This study explored how family religious environment and home teaching practices shape students’ Qur’anic reading fluency at SD 48 Kabupaten Sorong. A descriptive phenomenological qualitative design was employed, with participants selected through purposive and snowball sampling. Data were collected through in-depth semi-structured interviews, passive participant observation, and document study, then analyzed using Braun and Clarke’s six-phase thematic analysis. Findings from two key informants, a parent/guardian and a Qur’an teacher (ustadzah), revealed that consistent post-Maghrib recitation routines, parental modelling of reading and worship, the availability of iqra/qiroati materials, and a warm, low-pressure emotional climate at home were central to building children’s fluency and motivation. The Qur’an teacher emphasized that students whose families were religiously engaged progressed faster and retained tajwid rules more consistently than those relying solely on TPQ (Taman Pendidikan Al-Qur’an) instruction, although parents’ limited tajwid knowledge and time constraints were identified as recurring obstacles. The study concludes that the home functions as an informal Qur’anic literacy environment that complements formal instruction, and recommends collaborative parent–teacher–TPQ programs to strengthen this environment.